2009
DOI: 10.1152/ajpgi.90470.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteriprevents colitis by reducing P-selectin-associated leukocyte- and platelet-endothelial cell interactions

Abstract: Schreiber O, Petersson J, Phillipson M, Perry M, Roos S, Holm L. Lactobacillus reuteri prevents colitis by reducing P-selectin-associated leukocyte-and platelet-endothelial cell interactions. Am J Physiol Gastrointest Liver Physiol 296: G534 -G542, 2009. First published January 15, 2009 doi:10.1152/ajpgi.90470.2008.-Recent findings indicate that dextran sodium sulfate (DSS)-induced colitis is associated with a prothrombogenic phenotype, with P-selectin playing a major role in platelet recruitment. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…The rodent isolates 6799jm-1 (mouse) and R2LC (rat) outgrew all other strains and comprised around 97% of the total population on the forestomach epithelium, the natural niche of L. reuteri. This competition experiment confirmed earlier studies on the host specificity of L. reuteri strains in gut colonization (Molin et al, 1992;Carbajal et al, 1999;Schreiber et al, 2009), and together, the results clearly show that the phylogenetic relationships discovered for L. reuteri do reflect not only host origin but also ecological fitness.…”
Section: Reconstruction Of a More Accurate Genealogysupporting
confidence: 90%
See 1 more Smart Citation
“…The rodent isolates 6799jm-1 (mouse) and R2LC (rat) outgrew all other strains and comprised around 97% of the total population on the forestomach epithelium, the natural niche of L. reuteri. This competition experiment confirmed earlier studies on the host specificity of L. reuteri strains in gut colonization (Molin et al, 1992;Carbajal et al, 1999;Schreiber et al, 2009), and together, the results clearly show that the phylogenetic relationships discovered for L. reuteri do reflect not only host origin but also ecological fitness.…”
Section: Reconstruction Of a More Accurate Genealogysupporting
confidence: 90%
“…Such a 'joint' evolution would result in the development of generalists, which are promiscuous in terms of their ability to colonize the GITs of all members of these groups. In fact, this can be observed in L. reuteri isolates from mice and rats, which show comparable ecological performance in the mouse digestive tract (Figure 4 and references: Molin et al, 1992;Carbajal et al, 1999;Schreiber et al, 2009). In addition, murine Lactobacillus isolates show no host specificity in their adherence to epithelial tissues of mice and rats, whereas they generally do not adhere to epithelial cells of chickens and pigs (Savage, 1972;Lin and Savage, 1984;Tannock, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Host specialization is indeed reflected by the phenotypic characteristics of strains. Several experiments in animals showed that indigenous strains of L. reuteri outperform exogenous strains when competing in the gastrointestinal tract (63,(68)(69)(70)(71). Furthermore, the ability of L. reuteri strains to adhere to epithelia and epithelial cells in the proximal gut is to a large degree host-specific (53,54,72).…”
Section: Lactobacillus Reuteri As a Model Gut Symbiontmentioning
confidence: 99%
“…Empirical evidence for an immunoregulatory effect was achieved in several experimental models of colitis, where L. reuteri was highly efficient in reducing inflammation (70,71,(80)(81)(82). Immunomodulation has also been shown in humans, where L. reuteri ATCC 55730 has been shown to temporarily colonize the stomach and small intestine of healthy subjects and increase CD4 + T lymphocytes in the ileum (83).…”
Section: Making An Impact: Beneficial Effects Conferred By L Reuterimentioning
confidence: 99%
See 1 more Smart Citation